2023
DOI: 10.1086/723405
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of Activity Space in Marine Organisms across Latitudinal Gradients

Abstract: Unifying models have shown that the amount of space used by animals (e.g., activity space, home range) scales allometrically with body mass for terrestrial taxa; however, such relationships are far less clear for marine species. We compiled movement data from 1,596 individuals across 79 taxa collected using a continental passive acoustic telemetry network of acoustic receivers to assess allometric scaling of activity space. We found that ectothermic marine taxa do exhibit allometric scaling for activity space,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 93 publications
1
3
0
Order By: Relevance
“…Individual cumulative space use was found to scale allometrically with the body mass of individuals in both species, implying that larger individuals explored more space than smaller ones. This finding is consistent with the theoretical framework (McNab, 1963), and empirical studies (e.g., Cozzoli et al, 2022;Minns, 1995;Udyawer et al, 2022). Correspondingly, we observed that in both species, individuals with high SMR cumulatively explored a greater portion of the space and resource.…”
Section: Space Use Scaling With Body Mass and Smrsupporting
confidence: 91%
“…Individual cumulative space use was found to scale allometrically with the body mass of individuals in both species, implying that larger individuals explored more space than smaller ones. This finding is consistent with the theoretical framework (McNab, 1963), and empirical studies (e.g., Cozzoli et al, 2022;Minns, 1995;Udyawer et al, 2022). Correspondingly, we observed that in both species, individuals with high SMR cumulatively explored a greater portion of the space and resource.…”
Section: Space Use Scaling With Body Mass and Smrsupporting
confidence: 91%
“…acoustic tagging versus aquarium flume estimates or any other logging method with sufficient replicates) [ 18 ]. As more of these data accumulate and are archived in global databases [ 19 ], we recommend the calculation of ontogenetic allometries of swimming speed, using many different swimming metrics of the species. Ideally this would be augmented with measures of individual body mass.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that spawning cod displayed a lower fjord residency than non‐spawning individuals coincides with the size‐dependent behaviour observed in the feeding‐season sample, where larger cod were more likely to exit the fjords and remained resident for shorter time periods than their smaller conspecifics. Space use in animals is strongly linked to body size, both within and among species, with larger animals moving over larger spatial extents (Hopcraft et al, 2012; Rosten et al, 2016; Udyawer et al, 2023). Although we do not explicitly address the effect of body size on space use, it is likely that the negative correlation between fish length and fjord residency reflects greater movement capacity of larger individuals, due to greater swimming ability, greater energy demand, and higher trophic position than smaller cod.…”
Section: Discussionmentioning
confidence: 99%